APPLICATION of ENTROPY MULTICRITERIA METHOD FOR PARAMETRIC CLASSIFICATION of THE WIRE ELECTRICAL DISCHARGE MACHINING PROCESS USING NITINOL-60 SHAPE MEMORY ALLOY - Ogunmola, Bayo Yemisi; Onitiri, Modupe Adeoye; Alozie, Nehemiah Sabinus; Oluwo, Adeyinka; Okwo, Jeremiah Ugo; Rajan, John; Jose, Swaminathan; Oke, Sunday Ayoola; Aderibigbe, Samuel Bolaji (International Journal of Mechanical Engineering Technologies and Applications, 2025)
Nitinol-60 shape memory alloy (SMA) is known for its outstanding super elasticity non-magnetic properties, vibration absorption, high hardness and long fatigue life, among others. However, its conventional processing is difficult, complex and time-consuming, making the wire electrical discharge machining (WEDM) a viable option. Additionally, the choice of multicriteria methods is growing drastically in machining for economic and planning advantages. This paper presents an L15 orthogonal array analysis of the WEDM process parameters for nitinol-60 using the entropy method. The principal parameters are the gap voltage, dielectric flow rate and duty factor. However, the responses are surface crack density, recasting of larger thickness, and cutting rate. The procedure starts with the design of an experimental matrix with fifteen experiments. Then the parameters and responses are as beneficial and non-beneficial while their normalization is made. The entropy method is applied and the results are reported for the first time in the WEDM process of nitinol-60. to ensure optimum performance of the WEDM process, priority should be given in descending order to duty factor, dielectric flow rate and gap voltage at 0.1398, 0.1325 and 0.1117, respectively. to prioritize the responses, the average peak-to-valley height, maximum peak-to-valley heights and the cutting rate obtained the first, second and third positions, respectively. The findings presented in this work highlight the importance of nitinol-60 SMA as a promising candidate for medical devices and aerospace components. These are of public interest including neurovascular, dentistry, orthopedic, endoscopy and vascular intervention. It therefore offers new insights into planning in healthcare and wellbeing.